Artificial intelligence for smart patient care: transforming future of nursing practice - Hote, Payal Kahol; Venkatesan, Latha; Garg, Rakesh; Gopichandran, L. (International Journal of Research in Medical Sciences, 2023)
Artificial intelligence (AI) in today’s era has been described as “the new electricity” as it continually transforms today’s world by affecting our way of living in many different spheres. Extensive government programs in most countries and enhanced technology investments thereof are set to rapidly advance AI. Consequently, healthcare teams will be majorly affected by intelligent tools and systems to be launched into healthcare and patient homecare settings. AI represents a variety of functions under an umbrella of terms like machine learning (ML), deep learning, computer vision, natural language processing (NLP) and automated speech recognition (ASR) technologies. Each of these when used individually or in combination has the potential to add intelligence to applications. Understanding of AI in medical field is crucial for nurses. Utilization of AI in nursing will accelerate innovation and fasten up decision making for them thus saving their time and improving patient outcome plus satisfaction with nursing care provided. Of utmost importance while partnering with AI is the requirement for AI to be safe and effective. A major concern for AI practitioners in the current scenario is managing bias. To realize the full potential of AI, stakeholders (AI developers and users) need to be confident about two aspects: (1) reliability and validity of the datasets used and (2) transparency of AI based system. Issues encompassing AI are novel yet complex, and there is still much to be learnt about it. Nursing experience, knowledge, and skills will transit into new ways of thinking and processing information. This will give new roles to nurses-like information integrators, data managers, informatics specialists, health coaches and above all deliverers of compassionate caring-not replaced by AI technologies yet supported by them.